Symptom Recognition as a Mediator in the Self-Care of Chronic Illness - Riegel, Barbara; De Maria, Maddalena; Barbaranelli, Claudio; Matarese, Maria; Ausili, Davide; Stromberg, Anna; Vellone, Ercole; Jaarsma, Tiny (Frontiers in Public Health, 2022)
Background The recognition of a symptom is needed to initiate a decision to engage in a behavior to ameliorate the symptom. Yet, a surprising number of individuals fail to detect symptoms and delay in addressing early warnings of a health problem. Purpose The aim of this study was to test the hypothesis that symptom recognition mediates the relationship between monitoring for and management of symptoms of a chronic illness. Methods A secondary analysis of existing cross-sectional data. A sample of 1,629 patients diagnosed with one or more chronic conditions was enrolled in the United States (US) (n = 407), Italy (n = 784) and Sweden (n = 438) between March 2015 and May 2019. Data on self-care monitoring, symptom recognition, and self-care management was assessed using the Self-Care of Chronic Illness Inventory. After confirming metric invariance in cultural assessment, we used structural equation modeling to test a mediation model where symptom recognition was conceptualized as the mediator linking self-care monitoring and self-care management with autonomous (e.g., Change your activity level) and consulting behaviors (e.g., Call your healthcare provider for guidance). Results Symptom recognition mediated the relation between self-care monitoring and autonomous self-care management behaviors (β = 0.098, β = 0.122, β = 0.081, p < 0.001 for US, Italy, and Sweden, respectively). No mediation effect was found for consulting self-care management behaviors. Conclusion Our findings suggests that symptom recognition promotes autonomous self-care behaviors in people with a chronic condition. Self-care monitoring directly affects consulting self-care management behaviors but not through symptom recognition. Further research is needed to fully understand the role of symptom recognition in the self-care process.